Health insurance is associated with dental care use among university students in Washington State - Courtney M. Hill; Darragh Kerr; Donald L. Chi (BMC Oral Health, 2023)
Abstract Background The goal of this study was to examine the association of health insurance and preventive dental care use among university students. Methods This secondary analysis of cross-sectional data focused on students at University of Washington in Washington state (WA) who completed a health insurance survey in 2017 (n = 3768). The exposure was health insurance (private insurance in WA [reference group], not insured, Medicaid or Medicare [public insurance], university insurance, private insurance not in WA, other) and the outcome was receiving a dental cleaning in the past 6 months. Logistic regression was used to generate odds ratios and 95% confidence intervals (CI) adjusted for confounders. Results About 5% of university students did not have health insurance and 37% did not have a dental cleaning in the past 6 months. Compared to students with private health insurance based in WA, the odds of not receiving a dental cleaning were 3.90 times greater for university students with no health insurance (95% CI 2.74, 5.55; p < .001) and 3.08 times greater for publicly-insured university students (95% CI 2.52, 3.76; p < .001). Conclusions University students are at risk for poor oral health behaviors. Those without health insurance and those with public insurance face barriers to preventive dental care. Efforts should be made to connect uninsured university students with insurance, dental services, and other oral health promotion activities.